Community Case Study of Naloxone Distribution by Hospital-Based Harm Reduction Program for People Who Use Drugs in New York City - Riazi, Farah; Toribio, Wilma; Irani, Emaun; Hughes, Terence M.; Huxley-Reicher, Zina; McBratney, Elisa; Vu, Trang; Sigel, Keith; Weiss, Jeffrey J. (Frontiers in Sociology, 2021)
I. BACKGROUND In 2017, The Respectful & Equitable Access to Comprehensive Healthcare (REACH) Program at Mount Sinai Hospital became a registered Opioid Overdose Prevention Program (OOPP) and received funding from the New York City Department of Health and Mental Hygiene to develop a program to provide overdose education and naloxone distribution (OEND) training to at risk population and bystanders. We report on the programmatic quality improvement initiatives conducted. II. Methods From April 2017 to December 2020, the REACH OOPP conducted 290 opioid overdose reversal trainings, throughout the Mount Sinai Health System and in multiple other community settings. OEND training was at times offered alone and in other settings alongside Hepatitis C Virus point of care testing. Additionally, a “train the trainer” model was implemented whereby medical students and nurses at outpatient clinics were trained to train others. III. Results There were 4235 naloxone kits distributed to 3,906 participants. The training venues included hospital settings (patients and medical staff), public events, substance use programs, educational facilities, homeless prevention programs, faith-based organizations, alternative to incarceration programs, and community-based organizations. We implemented two types of training. During outreach sessions, we utilized one-on-one personalized sessions to train bystanders. When training clinic staff in the “train the trainer” model we utilized a standardized didactic presentation with slides. The two top reasons participants reported for being trained were “Just in case I see someone overdose” (59.3%) and “I'm worried that someone I know will overdose OR that I will overdose” (20.2%). IV. Conclusions The REACH program at Mount Sinai Hospital developed an effective model to train community bystanders and health care staff by leveraging administrative support and building on broader programmatic initiatives to promote drug user health and stigma-free care for people who use drugs. Hospitals do not currently mandate staff training or keeping naloxone stocked at inpatient units or outpatients clinics posing a challenge when implementing an OEND program in this setting. A recommended policy change needed to decrease overdose deaths is for hospitals to be required to implement systematic naloxone education and access for all health care personal and at risk patients.